The Effects of Watering Volume and Topping on the Fruit Quality of Two Melon Varieties in a Substrate Hydroponic System - Ajitama, Trio Fanny; Susila, Anas Dinnurohman; Suwarno, Willy Bayuardi (Journal of Tropical Crop Science, 2024)
Melons are horticultural fruits with increasing demand and high economic value. In 2020, the export demand for melons was 388.98 tons, with key destinations including Hong Kong, the United Arab Emirates, Qatar, Saudi Arabia, Germany, Malaysia, East Timor, and Singapore. However, quality degradation, such as fruit cracking, can negatively impact marketability. Dorais et al. (2004) identified several factors contributing to fruit splitting, including genetics, pruning time, water management (rain, high humidity, or intensive irrigation following drought), high temperatures, light, calcium content, and the strength of fruit cell walls. Effective and efficient cultivation practices are essential to mitigate these issues. This research aimed to determine the effect of watering volume and topping treatment on the growth and quality of two melon varieties in a substrate hydroponic system. The experiment was conducted from March 2021 to May 2021 in the greenhouse of the Leuwikopo IPB University Experimental Garden, located at an altitude of 218.79 meters above sea level. Two melon varieties were used: “Alisha” (V1) and “Glamour” (V2), with four replications for each treatment. The treatments were watering volume and topping. Watering consists of consistent watering volume of 250 ml per plant until harvest, variable watering volume according to the growth phase, i.e., 200 ml per plant, 300 ml per plant, and 350 ml per plant for phase, 1, 2, and 3, respectively. The effects of the treatments on all agronomic traits and fruit quality were assessed. The results showed that topping did not significantly affect any of the agronomic traits or fruit quality. Maintaining a consistent watering volume of 250 ml per plant until harvest is beneficial for the growth and quality of melon varieties “Alisha” and “Glamour” in a substrate hydroponic system. Effective water management is crucial in melon cultivation to ensure high-quality fruit production and minimize issues such as fruit cracking. Future research could explore additional factors influencing melon quality and yield to further optimize cultivation practices.